2017
DOI: 10.1007/s00264-017-3622-z
|View full text |Cite
|
Sign up to set email alerts
|

Gait analysis of patients with an off-the-shelf total knee replacement versus customized bi-compartmental knee replacement

Abstract: Introduction Newer TKR designs have been introduced to the market with the aim of overcoming common sizing problems with older TKR designs. Furthermore, since a sizable percentage of patients with OA present with disease limited to the medial/ lateral knee compartment in addition to the patellofemoral joint, for whom, a customized bi-compartmental knee replacement (BKR) is available as a treatment option. To date, there is very little information regarding knee strength and mechanics during gait for patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…have shown that knee-joint kinematics in patients with unilateral BKR replicate the kinematics of their contra-lateral non-involved limb and also that of healthy external controls. Wang et al [38] evaluated knee strength and biomechanics during walking in patients with BKR, TKR and healthy control subjects. They found that BKR patients reported higher satisfaction while performing activities of daily living and improved their quadriceps strength to a level that was close to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…have shown that knee-joint kinematics in patients with unilateral BKR replicate the kinematics of their contra-lateral non-involved limb and also that of healthy external controls. Wang et al [38] evaluated knee strength and biomechanics during walking in patients with BKR, TKR and healthy control subjects. They found that BKR patients reported higher satisfaction while performing activities of daily living and improved their quadriceps strength to a level that was close to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Patientspecific instrument has been developed to overcome the problems caused by altered geometry in variations in implant alignment. In short, effect of soft tissue, not an implant design, is important in nonweight bearing condition (44). The interest finding was the verification that customized TKA provides more normal-like healthy knee kinematics than standard OTS TKA does.…”
Section: Discussionmentioning
confidence: 99%
“…This trend was similar to previous study. In short, effect of soft tissue, not an implant design, is important in nonweight bearing condition (44). In addition, we recently showed bicruciate retaining TKA restored closer native knee kinematics using computational simulation (45).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies that focused on customized TKA are associated with good clinical reports, although most of them were limited to CR-TKA [ 18 20 , 22 ]. Previous studies did not focus on post-cam design in customized PS-TKA.…”
Section: Discussionmentioning
confidence: 99%